Prevalence of tissue transglutaminase antibodies and IgA deficiency are not increased in juvenile idiopathic arthritis: a case-control study - Angela Taneja Kohli; Aimee O. Hersh; Lori Ponder; Lai Hin Kimi Chan; Kelly A. Rouster-Stevens; Anne E. Tebo; Subra Kugathasan; Stephen L. Guthery; John F. Bohnsack; Sampath Prahalad (BMC, 2023)
Abstract Background The prevalence of Celiac Disease (CD) in Juvenile Idiopathic Arthritis (JIA) has been reported to be 0.1-7% in various small studies. As a result of the limited number of research and their inconclusive results there are no clear recommendations for routine CD screening in asymptomatic patients with JIA. Our aim is to estimate the prevalence of IgA deficiency and tissue transglutaminase (tTG) IgA in a cohort of JIA followed in two large academic medical centers. Methods Serum was collected and stored from all subjects and analyzed in a reference laboratory for total IgA (Quantitative Nephelometry) and tTG IgA antibody levels (Semi-Quantitative Enzyme-Linked Immunosorbent Assay). Fisher's exact tests were performed for statistical significance. Risk estimates (odds ratios) with 95% confidence intervals were calculated. Results 808 JIA cases and 140 controls were analyzed. Majority were non-Hispanic whites (72% vs. 68% p = 0.309). A total of 1.2% of cases were IgA deficient compared to none of the controls (p = 0.373). After excluding IgA deficient subjects, 2% of cases had tTG IgA ≥ 4u/mL compared to 3.6% of controls (p = 0.216) (OR = 0.5; 95% C.I = 0.1-1.4); and 0.8% of cases had tTG IgA > 10u/mL compared to 1.4% of controls (p = 0.627) (OR = 0.5; 95%C.I = 0.1-2.9). Conclusions Using the largest JIA cohort to date to investigate prevalence of celiac antibodies, the prevalence of positive tTG IgA was 0.8% and of IgA deficiency was 1.2%. The results did not demonstrate a higher prevalence of abnormal tTG IgA in JIA. The study did not support the routine screening of asymptomatic JIA patients for CD.